Five ways for facilitators to get a grip on small group learning - D'Eon, Marcel; Zhao, Rebecca (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Successful groups do not happen by chance, and they do not depend solely or even mainly on the interpersonal skills of the group members. Cooperative learning (CL) theory tells us that small groups are successful when facilitators structure and organize the small group to include each one of the five elements of cooperative learning. In this article, we have described each of these five elements as a way to get a grip on small group learning: positive interdependence, promotive interaction, group and individual accountability, interpersonal and small group skills, and group processing. To help our readers remember the five key elements of CL, the five ways to get a grip on small group facilitation, we have created an infographic.